2022
DOI: 10.1002/hsr2.496
|View full text |Cite
|
Sign up to set email alerts
|

Visual representations of SARS‐CoV‐2, emotions, and risk perception of COVID‐19

Abstract: Background and Aims Before COVID‐19 was declared a global pandemic, the U.S. Centers for Disease Control and Prevention (CDC), the National Institute of Allergy and Infectious Diseases (NIAID), and many other organizations published many images of its pathogen (namely SARS‐CoV‐2) to raise public awareness of the disease. Despite their scientific and aesthetic values, such images may convey metaphoric meanings and cause a subsequent impact on viewers' fear and disgust. This study investigated how exposure to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…However, it is worth noting that some visual characteristics, such as the repetitive use of circular shapes and the juxtaposition of contrasting colors, can elicit strong negative emotional responses (Ayzenberg et al, 2018; Rádlová et al, 2019). For instance, a study examining visual representations of SARS-CoV-2 (the pathogen responsible for causing COVID-19) found that images characterized by vibrant colors, irregular shapes, and sophisticated patterns evoked stronger emotions, including fear and disgust, among viewers than those lacking these distinctive features (N. Li et al, 2022).…”
Section: Visual Art and Emotional Responses To Science Issuesmentioning
confidence: 99%
“…However, it is worth noting that some visual characteristics, such as the repetitive use of circular shapes and the juxtaposition of contrasting colors, can elicit strong negative emotional responses (Ayzenberg et al, 2018; Rádlová et al, 2019). For instance, a study examining visual representations of SARS-CoV-2 (the pathogen responsible for causing COVID-19) found that images characterized by vibrant colors, irregular shapes, and sophisticated patterns evoked stronger emotions, including fear and disgust, among viewers than those lacking these distinctive features (N. Li et al, 2022).…”
Section: Visual Art and Emotional Responses To Science Issuesmentioning
confidence: 99%